2005
DOI: 10.1300/j200v03n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Case Management Services

Abstract: Specialized programs for pregnant, drug dependent women have assisted many in achieving abstinence during pregnancy. Following delivery, however, such women often resume drug use and drop out of treatment, placing their children at even greater risk for subsequent medical and developmental problems. Standard outreach services, while generally effective as a public health measure for high-risk populations of women and children, are often insufficient for chronic and severely drug dependent women. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Of the 15 clinical trials with personal functioning outcomes, all but four had positive effect sizes that ranged from 0.003 (53) to 0.608 (62) (see Figure 5). Three studies had a very small negative effect size for functioning outcomes (12, 36, 49), but one study reported a negative effect size of −0.34 (64).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 15 clinical trials with personal functioning outcomes, all but four had positive effect sizes that ranged from 0.003 (53) to 0.608 (62) (see Figure 5). Three studies had a very small negative effect size for functioning outcomes (12, 36, 49), but one study reported a negative effect size of −0.34 (64).…”
Section: Resultsmentioning
confidence: 99%
“…Expanded case management services have been frequently applied among substance users with additional mental health (82, 83) and HIV/AIDS problems (49, 84). It is a standard part of comprehensive case management models like intensive case management (53, 55) and Assertive Community Treatment (ACT) (54, 64). Importantly, various studies were excluded from this review, as they offered comprehensive interventions combining case management with other viable approaches (e.g., cognitive behavioral therapy, Housing First programs), in which case management effects could not be disentangled from these additional interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In two of the trials, models of case management were compared with one another (Essock et al, 2006;Jansson, Svikis, Breon, & Cieslak, 2005;Manuel, Covell, Jackson, & Essock, 2011).…”
Section: Data Extraction and Preparationmentioning
confidence: 99%
“…In comparing dosage of strengths case management across three conditions (delivered within drug treatment programs, delivered by an outside service agency, and delivered by telephone), Huber et al (2003) reported that, within the first 90 days of the intervention, the mean number of hours of contact ranged from 3.0 to 3.2 and the mean number of sessions attended ranged from 3.5 to 5.7. Jansson et al (2005) compared routine case management for drug-dependent women and their newborns with intensive case management that involved additional and more frequent contact with the mother and infant. Over the 4-month intervention, women in routine case management attended a mean of 1.6 sessions (range = 0 to 4), whereas those in intensified case management attended a mean of 5.8 visits (range = 0 to 9).…”
Section: Session Adherence In Behavioral Treatment Interventionsmentioning
confidence: 99%